Efek Mediasi Emotional Condition pada Pengaruh Display Product dan Store Atmosphere terhadap Impulse Buying - Devi, Sri; Halijah, Siti Nur; Sarwoto, Sarwoto; Batubara, Rizki Wulanita (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to determine the effect of product display and store atmosphere on emotional conditions and their implications on impulse buying. The research method used is a quantitative method with Smart PLS 3.0 software. The population in this study were buyers of Irian Supermarket & Dept. Store Tebing Tinggi who made impulse buying, but the exact number is unknown. Determination of the number of samples using the Cochran formula, the sampling technique used was non-probability sampling with accidental sampling technique. Data collection using a questionnaire with a sample of 97 respondents. The results of the outer model test showed that the instrument was valid and reliable as seen from the cross loading table and construct reliability and validity. The inner model test showed that the Z determinant coefficient value was 0.418 and the Y determinant coefficient was 0.251. The results of the hypothesis test showed that product display had no effect on impulse buying, store atmosphere had no effect on impulse buying. Product display had an effect on emotional conditions, store atmosphere had an effect on emotional conditions, emotional conditions had an effect on impulse buying, and emotional conditions were mediating variables in the effect of product display and store atmosphere on impulse buying.